Impact of development of the village settlement in urban area case study: Kampung Sungai Pusu, Gombak, Selangor / Mohd Ulul Azmi Abd Hamid - Abd Hamid, Mohd Ulul Azmi (2010)
Urban fringe is a part of area that has received the impact while urban has been experiencing development growth to achieve the sustainable development. The experience helped this area to develop the contents to reach their goal and objective of existence of the settlement. In this case, especially for village settlements that located in urban fringe area are being hemmed by the urban overspill. Many characteristic and factors will be influenced and affected when involve this situation. In developing countries, a substantial and growing proportion lives in or around metropolitan areas and mega cities, including the zone termed the „urban fringe‟, where their livelihoods depend to some extent on natural resources such as land for food, water and fuel and space for living. This study would be identified the deepness and wideness of impact and through these approaches it can be used for the future to make it balance between urban and suburban development. In order this study reach the objective, there are 150 respondents and involving around 50 variables in questionnaire form. In this case, Statistical Package for Social Sciences (SPSS) software version 16 is used to generate the analysis and meets the result. More detail findings indicated that the urban overspill in the urban outskirt has given some impact on the physical and socio-economic aspect. Location is a main factor contributing the changes of traditional entities at village in urban fringe area. The consequence of urban development is some of the development project has replaced the agricultural land to the residential land. That will increase its population and make the area be crowded. It is because, the residential developed is still circulated in the same existed area. In conclusion, overall of physical and socio-economic impact for this area is not aggressively even though this area is located edge of city center